2021
DOI: 10.3390/ani11082186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Niacin on Growth Performance, Intestinal Morphology, Mucosal Immunity and Microbiota Composition in Weaned Piglets

Abstract: This study aimed to investigate the effects of niacin on growth performance, intestinal morphology, intestinal mucosal immunity, and colonic microbiota in weaned piglets. A total of 96 weaned piglets (Duroc × (Landrace × Yorkshire), 21-d old, 6.65 ± 0.02 kg body weight (BW)) were randomly allocated into 3 treatment groups (8 replicate pens per treatment, each pen containing 4 males; n = 32/treatment) for 14 d. Piglets were fed a control diet (CON) or the CON diet supplemented with 20.4 mg/kg niacin (NA) or an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The sodium butyrate and niacin diet can alleviate diarrhoea symptoms and increase growth performance in pigs (Liu et al, 2021; Sun et al, 2020). In our study, sodium butyrate and niacin were reported to be harmless to the body, even at high doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sodium butyrate and niacin diet can alleviate diarrhoea symptoms and increase growth performance in pigs (Liu et al, 2021; Sun et al, 2020). In our study, sodium butyrate and niacin were reported to be harmless to the body, even at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…During the weaning period, weaning causes reductions in intestinal immunity and Vitamin B metabolism, resulting in susceptibility to diarrhoea and growth obstruction (Hu et al, 2013; Smith et al, 2010). Various studies have documented that butyric acid and niacin are often used in swine production to improve the intestinal health and growth performance of piglets (Feng et al, 2018; Liu et al, 2021). Butyric acid is involved in multiple physiological processes of primary importance for growth, such as immune modulation, Vitamin B metabolism and intestinal microbiota composition (Chen et al, 2019; Leonel & Alvarez‐Leite, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative changes in some specific bacteria in the present study were supported by previous studies. Studies have pointed out that the abundance levels of Halomonas , Peptococcus , and Rubrobacter can be associated with intestinal inflammation, and are increased when intestinal inflammation occurs [ 36 , 37 , 38 ]. Streptomyces and Micromonospora , as members of Actinobacteria , have been shown to have anti-inflammatory and antioxidant effects [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings indicated that AQPs may be potential targets for attenuation of diarrhea. As a common feed additive in pig farming, niacin has been shown to improve the intestinal health of weaned piglets [ 22 , 23 ]. However, the relationship between niacin-mediated alleviation of the weaning stress-induced diarrhea and the changes in AQPs expression, and the underlying mechanism needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that GPR109 is expressed in intestinal epithelial cells and has a role in regulating microbial metabolism, inhibiting colonic inflammation, and maintaining the integrity of the intestinal barrier [ 25 , 26 ]. Furthermore, supplements with niacin can increase the relative abundance of probiotics in the colon, and alleviate the inflammatory response in the small intestine via GPR109A [ 23 ]. However, limited information regarding whether niacin directly regulates the expression of AQPs in weaned piglets via GPR109A.…”
Section: Introductionmentioning
confidence: 99%